2015
DOI: 10.1002/tesj.211
|View full text |Cite
|
Sign up to set email alerts
|

In-Service Teachers' Perspectives on Adolescent ELL Writing Instruction

Abstract: As writing has assumed increasing importance in discussions of pedagogy for diverse classrooms, attention to the contexts in which secondary teachers develop and implement writing instruction for adolescent English language learners (ELLs) is of great importance. Drawing on ecological language learning theories and situated teacher learning theory (van Lier, 2003;Borko, 2004), the authors present findings from participants in a focus group (N = 10) and follow-up interviews (N = 6) conducted with a set of secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…Lack of writing pedagogy skills. A lack of writing pedagogy skills revolves around issues related to stating the expectations of writing tasks explicitly, aligning teachers' understanding and expectations of writing with those of students, good practices in error correction, feedback, and assessment, providing responsive assessment and strategic scaffolding, addressing individual student needs and skills development, use of metalanguage, skills and knowledge to recognize different identities of L2 writers and their specific strengths and weaknesses, and the ability to scrutinize ESL writers' work (Enright & Gilliland, 2011;Kibler, 2011b;Kibler et al, 2016;Larsen, 2013Larsen, , 2016Ortmeier-Hooper, 2013;Shin, 2016;Wong, 2016). Kibler (2011b) found that tenth grade teachers' expectations about writing tasks were at best implicit, and they shared their expectations with students only through feedback as opposed to explicit "lessons focused on writing" (p. 223).…”
Section: Rq1: What Challenges Do Teachers Encounter In Teaching Esl Writing In K-12 Contexts?mentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of writing pedagogy skills. A lack of writing pedagogy skills revolves around issues related to stating the expectations of writing tasks explicitly, aligning teachers' understanding and expectations of writing with those of students, good practices in error correction, feedback, and assessment, providing responsive assessment and strategic scaffolding, addressing individual student needs and skills development, use of metalanguage, skills and knowledge to recognize different identities of L2 writers and their specific strengths and weaknesses, and the ability to scrutinize ESL writers' work (Enright & Gilliland, 2011;Kibler, 2011b;Kibler et al, 2016;Larsen, 2013Larsen, , 2016Ortmeier-Hooper, 2013;Shin, 2016;Wong, 2016). Kibler (2011b) found that tenth grade teachers' expectations about writing tasks were at best implicit, and they shared their expectations with students only through feedback as opposed to explicit "lessons focused on writing" (p. 223).…”
Section: Rq1: What Challenges Do Teachers Encounter In Teaching Esl Writing In K-12 Contexts?mentioning
confidence: 99%
“…Consequently, students' skills for content area writing were underdeveloped. Other studies underlined the importance of teachers' in-depth knowledge of L2 writing pedagogy and assessment practices (Kibler et al, 2016;Larsen, 2016;Wong, 2016) as well as a need for "responsive assessment, instruction, and strategic scaffolding" (Wong, 2016, p. 64). Enright and Gilliland (2011) found that ESL writing teachers did not focus on addressing students' individual needs or skill development.…”
Section: Rq1: What Challenges Do Teachers Encounter In Teaching Esl Writing In K-12 Contexts?mentioning
confidence: 99%
See 2 more Smart Citations
“…All teachers (content‐area and ELL) are responsible for teaching ELLs and helping them be successful. Shared responsibility “describe[s] the mind‐set that all educators see themselves as equal stakeholders who must strive to positively influence the education of ELLs in the classroom as well as outside of school” (Staehr Fenner, , p. 29), even though there might be tensions between which teacher (content‐area or ELL) is responsible and/or qualified to teach the content and/or the language to ELLs (Kibler, Heny, & Andrei, ). In addition, content‐area teachers might not be prepared to teach ELLs in their classes (Ballantyne et al., ); they might need time, support, and varied learning experiences to integrate new learnings and skills that allow them to serve the ELLs in their classroom (Daniel & Pray, ).…”
Section: Introductionmentioning
confidence: 99%